Preparation method and application of fuel cell catalyst
Preparation of Pt catalysts with hollow nanocrystalline structures by sol-gel method solves the problems of complex process, high cost and insufficient stability in the prior art, and achieves high performance, stability and environmentally friendly fuel cell catalyst preparation.
Patent Information
- Application Number
- CN202411849253.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The existing fuel cell catalysts have complex preparation processes, high cost, unfriendly environment, and the limited and incomplete removal of precious metals lead to insufficient stability and durability of the catalyst.
The Pt catalyst with hollow nanocrystalline structure was prepared by sol-gel method, and through magnetic stirring, heat treatment, liquid phase loading and gas phase reduction, an internal bridged multi-stage framework structure was constructed to simplify the process and reduce costs.
It realizes the high performance and stability of the catalyst, improves the activity and durability of the oxygen reduction reaction, simplifies the preparation process, reduces the equipment cost and environmental impact, and is suitable for large-scale mass production.
Smart Images

Figure CN119674103A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a preparation method and application of a fuel cell catalyst. Background Art
[0002] By 2040, global energy demand is expected to increase by 90% from current levels, and currently only 28% of global electricity generation comes from renewable energy. In order to meet this energy demand, it is imperative and time is running out to increase renewable energy and adopt low-carbon energy generation technologies. Fuel cells play an important role both as energy storage and power generation systems. The high energy density of fuel cell systems makes them suitable for a wide range of fields, such as long-distance transportation and stationary power stations. In these fields, they can work in conjunction with other electrochemical power sources such as batteries and supercapacitors. Therefore, achieving high-performance and low-cost fuel cells can provide an important way to establish a low-carbon and sustainable future for the earth.
[0003] The cathode oxygen reduction reaction of the fuel cell membrane electrode is a reaction process involving four electron transfer. At present, in the industrial field, based on the requirements for membrane electrode reliability and durability, Pt / C is still the most important oxygen reduction reaction (ORR) catalyst, but the distribution of Pt precious metals on the earth is limited. In recent years, scholars from all walks of life have focused their work on how to reduce the precious metal loading while improving the activity and stability of the catalyst. At present, an effective method is to form a specific morphology and molecular structure through crystal phase engineering and interface engineering to achieve the exposure of a specific crystal form on the metal surface. On the other hand, the center position of the Pt atom d band is changed through electronic effects and stress effects, thereby regulating the adsorption and desorption energy of each intermediate oxygen-containing product on the catalyst active site during the ORR reaction process, thereby improving the catalyst activity. Among them, catalysts with characteristic morphology, such as core-shell structure and hollow nanocrystals, are generally synthesized by sacrificial template preparation process. The template is generally purchased from other precious metals or transition metal elements, which will cause the catalyst synthesis process to be complicated, cost-increasing, and environmentally unfriendly. What's more, if the transition metal is not completely cleaned during the removal process, even a trace amount of residue will damage the proton membrane of the fuel cell membrane electrode and the ionomer in the catalyst layer. Therefore, it is urgent to develop a preparation process for fuel cell oxygen reduction catalysts that is simple to operate, low in energy consumption, stable and reliable in product structure, and can be used for large-scale mass production. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a fuel cell catalyst, which has a simple and easy-to-operate preparation process, low equipment cost and maintenance cost, is environmentally friendly, and is easy to realize industrial continuous mass production.
[0005] The technical solution of the present invention is achieved in this way: The present invention provides a method for preparing a fuel cell catalyst, comprising the following steps: S1: adding a platinum precursor solution, a first solvent and a second solvent in sequence, stirring the mixture by magnetic stirring until the mixture reaches a clear state, and allowing the mixture to stand and age at room temperature to obtain a sol-gel; S2: placing the sol-gel obtained above in a muffle furnace for heat treatment, then naturally cooling to room temperature, taking out the calcined powder, grinding it, washing it and drying it; S3: taking the above powder and carbon carrier, adding a third solvent and a dispersing aid, dispersing by emulsification shearing in an ice-water bath, and then filtering and drying; S4: placing the cleaned powder in a tubular furnace, introducing a reducing atmosphere, heating for reduction, cooling to room temperature, taking out the powder, cleaning and drying, and obtaining a supported hollow structured Pt catalyst powder.
[0006] As a further improvement of the present invention, the rotation speed of the magnetic stirring in step S1 is 100-300 rpm, the stirring time is 3-6 hours, and the static aging time is 8-24 hours.
[0007] As a further improvement of the present invention, the precious metal precursor solution in step S1 is one or more of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, and platinum nitrate; the first solvent is one or more of anhydrous ethanol, methanol, propanol, and ethylene glycol; the second solvent is one or more of diethanolamine, oleylamine, triethanolamine, and ethanolamine.
[0008] As a further improvement of the present invention, the heating rate of the heat treatment in step S2 is 1-10°C / min, and the temperature is heated to 50-150°C and then kept warm for 2-12h.
[0009] As a further improvement of the present invention, the shearing speed in step S3 is 10000-30000 rpm, and the shearing time is 1-6 hours.
[0010] As a further improvement of the present invention, the carbon carrier in step S3 is one or more of commercial carbon black, acetylene black, carbon nanotubes, and graphite carbon; the third solvent is one or more of anhydrous ethanol, methanol, propanol, and ethylene glycol; and the dispersing aid is one or more of sodium dodecyl sulfate, alkyl sulfonates, and sodium dodecylbenzene sulfonate.
[0011] As a further improvement of the present invention, the heating reduction in step S4 is performed at a heating rate of 5-15°C / min, and the temperature is kept at 100-300°C for 1-4h.
[0012] As a further improvement of the present invention, the filtering method adopts one or more of positive pressure filtration, membrane filtration, and centrifugal filtration; the drying method adopts one or more of vacuum drying, freeze drying, and electric heating blast drying.
[0013] The present invention further protects a fuel cell catalyst prepared by the above preparation method.
[0014] The present invention further protects the use of the above fuel cell catalyst in the preparation of a fuel cell.
[0015] The present invention has the following beneficial effects: (1) The sol-gel preparation process is used to construct a hollow nanocrystal structure. The multi-level framework structure that is bridged internally is the fundamental reason for improving the performance of the catalyst. The performance and durability of hollow bridged platinum nanocrystals are mainly due to the improvement of the surface energy of the nanocrystals and the formation of an antioxidant surface morphology brought about by the lattice contraction / lattice stress strain induced by the hollow structure. At the same time, the hollow nanostructure further increases the specific surface area of the nanomaterial, and increasing the surface active sites with high coordination numbers is very important for improving the activity and stability of the oxygen reduction reaction.
[0016] (2) The catalyst preparation process is simple and easy to operate, has low equipment cost and maintenance cost, is environmentally friendly, and is easy to achieve industrial continuous mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0018] Figure 1 This is a schematic diagram of the structure of the catalyst product prepared in Example 1; Figure 2 The membrane electrode prepared by the catalyst provided in Example 1 is at 25 cm 2 IV performance change curve of the performance test process before and after catalyst aging on a single cell. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1 S1: Metal sol-gel. Add 74 mL of 0.39 mol / L chloroplatinic acid solution, 40 mL of anhydrous ethanol and 13.4 mL of diethanolamine in a screw-necked flask, stir at 300 rpm with magnetic stirring for 6 h until the mixture reaches a clear state. Allow to stand for aging at room temperature for 12 h to obtain a metal sol-gel.
[0021] S2: Low-temperature calcination. The sol-gel obtained above was placed in a muffle furnace for heat treatment. The program heating rate was set to 2°C / min. After heating to 130°C, it was kept warm for 4 hours and then naturally cooled to room temperature. The calcined powder was taken out and ground, washed with deionized water and dried.
[0022] S3: Liquid phase loading: Take 0.63g of the above powder and 0.5g of porous conductive carbon black, add 10mL of deionized water, 100mL of anhydrous ethanol and 0.05g of sodium dodecyl sulfate in sequence, and use emulsification shear dispersion under ice water bath conditions, with a shear speed of 10000rpm and a shear time of 2h, then filter and dry.
[0023] S4: Gas phase reduction. Place the cleaned powder in a tube furnace and introduce hydrogen. Set the program heating rate to 10°C / min, heat to 280°C and keep warm for 3 hours, then cool naturally to room temperature. Take out the powder, wash it with deionized water and dry it. Obtain a supported hollow structure Pt catalyst powder. Figure 1 This is a schematic diagram of the structure of the catalyst product prepared in Example 1; Figure 2 The membrane electrode prepared by the catalyst provided in Example 1 is at 25 cm 2 IV performance change curve of the performance test process before and after catalyst aging on a single cell.
[0024] Embodiment 2-9 The differences between Examples 2-9 and Example 1 are that the raw materials and process parameters in the catalyst preparation method are different, see Table 1 for details.
[0025] Table 1
[0026] Comparative Example 1 S1: Take 74mL of 0.39mol / L chloroplatinic acid solution, 0.5g of porous conductive carbon black, add 10mL of deionized water, 100mL of anhydrous ethanol and 0.05g of sodium dodecyl sulfate in sequence, and use emulsification shear dispersion under ice water bath conditions, with a shear speed of 10000rpm and a shear time of 2h, then filter and dry.
[0027] S2: Place the cleaned powder in a tube furnace and introduce hydrogen. Set the program heating rate to 10°C / min, heat to 280°C and keep warm for 3 hours, then cool naturally to room temperature. Take out the powder, wash it with deionized water and dry it. Obtain the supported Pt catalyst powder.
[0028] Comparative Example 2 S1: Metal sol-gel. Add 74 mL of 0.39 mol / L chloroplatinic acid solution, 40 mL of anhydrous ethanol and 13.4 mL of diethanolamine in a screw-necked flask, stir at 300 rpm with magnetic stirring for 6 h until the mixture reaches a clear state. Allow to stand for aging at room temperature for 12 h to obtain a metal sol-gel.
[0029] S2: Low-temperature calcination. The sol-gel obtained above was placed in a muffle furnace for heat treatment. The program heating rate was set to 2°C / min. After heating to 130°C, it was kept warm for 4 hours and then naturally cooled to room temperature. The calcined powder was taken out and ground, washed with deionized water and dried.
[0030] S3: Liquid phase loading: 0.63 g of the above powder and 0.5 g of porous conductive carbon black were added to 110 mL of deionized water, and emulsified shear dispersion was performed in an ice-water bath at a shear rate of 10,000 rpm for 2 h, followed by filtration and drying.
[0031] S4: Gas phase reduction. Place the cleaned powder in a tube furnace and introduce hydrogen. Set the program heating rate to 10°C / min, heat to 280°C and keep warm for 3 hours, then cool naturally to room temperature. Take out the powder, wash it with deionized water and dry it. Obtain a supported hollow structure Pt catalyst powder.
[0032] Test Example 1 The catalysts prepared in Examples 1-9 and Comparative Examples 1-2 were applied to a half-cell to test the electrochemical active area; Half-cell electrode preparation: A: The volume ratio of the solution is V IPA :V H2O :V Nafion =4:1:0.016 to prepare ionomer dispersion; B: 5 mg of catalyst was added into 5 mL of ionomer dispersion A and ultrasonicated for 10 min; C: 10 μL was drop-coated on a platinum carbon electrode, and after drying, it was tested in a 0.5MH2SO4 solution saturated with N2.
[0033] The catalysts prepared in Examples 1-9 and Comparative Examples 1-2 were applied to membrane electrodes.
[0034] Preparation method of membrane electrode: take 0.5g catalyst powder (corresponding to the catalysts prepared in Examples 1-8 and Comparative Examples 1-2, respectively), add 0.25g nafion membrane solution containing ionomer, and 40g mixed solution of ethanol and water (Vethanol:Vwater=4:1), use a high-speed shear emulsifier to disperse in an ice water bath at 8000rpm for 30min, then use an ultrasonic atomization sprayer to spray 0.40mg / cm2 on the cathode side of the proton membrane, and spray Pt / C catalyst on the anode side with a loading of 0.02mg / cm2, and obtain the membrane electrode sample to be tested after bonding the frame, carbon paper and packaging.
[0035] Membrane electrode performance test plan: high-purity hydrogen (1.5L / min) is distributed to the anode and air (2L / min) is distributed to the cathode. The relative humidity of the anode is set to 20%, the humidity of the cathode is set to 50%, the anode stack pressure is 80kpa, the cathode stack pressure is 70kpa, and the stack temperature is 75°C. Load to the maximum current and activate at a constant current for 30 minutes under hydrogen and oxygen conditions, then switch the cathode to air, wait for the voltage to stabilize for about 15 minutes, and test the initial (BOL) VI performance of the membrane electrode.
[0036] High-purity hydrogen (0.5L / min) was distributed to the anode and air (0.5L / min) was distributed to the cathode. The anode relative humidity was set to 45%, the cathode humidity was set to 45%, the anode stack pressure was 50kPa, the cathode stack pressure was 50kPa, the stack temperature was 60°C, and the initial ECSA of the membrane electrode was obtained through testing.
[0037] Hydrogen (0.2L / min) was distributed to the anode and nitrogen (0.075L / min) was distributed to the cathode. The relative humidity of the cathode and anode was set to 100%, the pressure of the cathode and anode inlet was normal pressure, and the stack temperature was 80°C. A square wave cycle of 0.6V for 3s and 0.95V for 3s was performed to perform a catalyst aging test to obtain the initial (EOL) VI performance of the membrane electrode. "BOL" refers to the hydrogen / air I / V-polarization measurement result before the catalyst aging test, and "EOL" refers to the hydrogen / air I / V-polarization measurement result after the catalyst aging test.
[0038] The performance of the catalysts of Examples 1-9 and Comparative Examples 1-2 and the corresponding half-cells and membrane electrode (MEA) are summarized in Table 2.
[0039] Table 2
[0040] The embodiments of the present invention can prepare Pt / C catalysts with hollow nanocrystals and internal bridged multi-level framework structures. In particular, Embodiment 1 exhibits excellent electrocatalytic initial activity of 0.687V@2A / cm2 and catalyst durability under potential cycling conditions of 0.6-0.95V. After potential cycling aging, the voltage drop under 1A / cm2 is only 7mV, and the electrochemical active area (ECSA) in MEA drops by only 6% at EOT. This can greatly help achieve the durability goal of 30,000 hours of design life of fuel cell membrane electrodes in commercial vehicles.
[0041] Further analysis of Table 1 and Table 2 shows that, in the preparation step (1), a uniformly dispersed and preliminarily stable metal sol-gel can be obtained within the range of appropriate stirring speed, stirring time and aging time. In step (2), a metal oxide with an internally bridged multi-stage framework structure can be obtained under appropriate calcination process conditions. Subsequently, in step (3), with the assistance of appropriate solvents and dispersants, uniform mixing and dispersion of metal nanocrystals and carriers is achieved. From Examples 8-9, it can be concluded that in the gas phase reduction reaction process of the present invention, appropriate reaction temperature and reaction time have a strong correlation effect on the activity and durability of the reaction product. When the reaction time is too short, the multi-stage bridge structure is insufficient to be fully formed, the specific surface area of the catalyst is reduced, and accordingly, the catalytic reaction activity is reduced. When the reaction temperature is too low, a regular and orderly hollow structure cannot be formed, the lattice stress contraction effect is not obvious, and the surface of the nanocrystal is not resistant to oxidation, which reduces the durability of the catalyst during the potential cycle.
[0042] From the comparison of the embodiment and comparative example 1 in Table 2, it can be concluded that when the sol-gel preparation process is not used in the catalyst preparation process, the prepared Pt / C catalyst does not have an internally bridged central control multi-level framework structure. Accordingly, both the initial performance and the aging performance are greatly reduced compared with the catalyst prepared in Example 1, with an initial performance reduction of 106 mV and an aging performance loss of about 14.6 times. By comparing the embodiment and comparative example 2, it can be concluded that when appropriate solvents and dispersants are not added during the liquid phase loading process, uniform mixing and dispersion of metal nanocrystals and carriers cannot be achieved, and the prepared Pt / C catalyst loses a regular and uniform morphology. Accordingly, the performance and durability of the prepared catalyst will both decrease, and the initial performance of the catalyst prepared in Example 1 is reduced by 66 mV, and the electrochemical active area loss is about 8.8 times.
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a fuel cell catalyst, characterized in that: The following steps are involved: S1: adding a platinum precursor solution, a first solvent and a second solvent in sequence, stirring the mixture by magnetic stirring until the mixture reaches a clear state, and allowing the mixture to stand and age at room temperature to obtain a sol-gel; S2: placing the sol-gel obtained above in a muffle furnace for heat treatment, then naturally cooling to room temperature, taking out the calcined powder, grinding it, washing it and drying it; S3: taking the above powder and carbon carrier, adding a third solvent and a dispersing aid, dispersing by emulsification shearing in an ice-water bath, and then filtering and drying; S4: placing the cleaned powder in a tubular furnace, introducing a reducing atmosphere, heating for reduction, cooling to room temperature, taking out the powder, cleaning and drying, and obtaining a supported hollow structured Pt catalyst powder.
2. The preparation method according to claim 1, characterized in that: The rotation speed of the magnetic stirring in step S1 is 100-300 rpm, the stirring time is 3-6 hours, and the static aging time is 8-24 hours.
3. The preparation method according to claim 1, characterized in that: The platinum precursor solution in step S1 is one or more of chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, and platinum nitrate; the first solvent is one or more of anhydrous ethanol, methanol, propanol, and ethylene glycol; the second solvent is one or more of diethanolamine, oleylamine, triethanolamine, and ethanolamine.
4. The preparation method according to claim 1, characterized in that: The heating rate of the heat treatment in step S2 is 1-10°C / min, and the temperature is heated to 50-150°C and then kept warm for 2-12h.
5. The preparation method according to claim 1, characterized in that: The shearing speed in step S3 is 10000-30000 rpm, and the shearing time is 1-6 hours.
6. The preparation method according to claim 1, characterized in that: In step S3, the carbon carrier is one or more of commercial carbon black, acetylene black, carbon nanotubes, and graphite carbon; the third solvent is one or more of anhydrous ethanol, methanol, propanol, and ethylene glycol; and the dispersing aid is one or more of sodium dodecyl sulfate, alkyl sulfonate, and sodium dodecylbenzene sulfonate.
7. The preparation method according to claim 1, characterized in that: The heating reduction in step S4 is carried out at a heating rate of 5-15°C / min, and the temperature is kept at 100-300°C for 1-4h.
8. The preparation method according to claim 1, characterized in that: The filtering method adopts one or more of positive pressure filtration, membrane filtration, and centrifugal filtration; the drying method adopts one or more of vacuum drying, freeze drying, and electric heating blast drying.
9. A fuel cell catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the fuel cell catalyst according to claim 9 in preparing a fuel cell.